PENGARUH SIMULASI TRANSPORTASI KAPAL PADA KERENTANAN KERANG HIJAU Perna viridis TERHADAP HYPOSALINITY - Yasser Ahmed; Dian Respati Widianari (Universitas Gadjah Mada, 2016)
Introduced species are species which exceed their natural distribution limits (native range) by a certain mode of introduction (vector). Natural movements are responsible to a limited extent. Introduction of a species could influence the susceptibility of a species to environmental stress no matter if introduced purposely or un purposely. Introduction of species could happen by natural movement i.e. organism can movement influenced by current and some organism can migrate to one area to another area; and human activity either purposely i.e. aquarium trade, aquaculture or un purposely such as accidentally through fouling on ship hulls. However, a dominant vector which has large contribution on species introduction is transported by ship hulls and ballast water tanks. Furthermore, the objective of this experiment is to investigate whether the organism can increase their tolerance during transport. The experimental design to mimicking transport condition in short term lab experiment and compared pre-stress group and non-stress group on the second stress. Afterward, looking forward the survival of the organism. Chosen of Green Mussels (P. viridis) from Muara Kamal, Jakarta Bay, and hyposaline stress. The response variable these experiments are survival and byssus. The results of this study showed that the group of pre-stress and non-stress group was no difference in the simulation of transport for survival. Byssus thread increase when recovery long enough and decrease when getting double stress.